If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + w = 2w Solving -2 + w = 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -2 + w + -2w = 2w + -2w Combine like terms: w + -2w = -1w -2 + -1w = 2w + -2w Combine like terms: 2w + -2w = 0 -2 + -1w = 0 Add '2' to each side of the equation. -2 + 2 + -1w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1w = 0 + 2 -1w = 0 + 2 Combine like terms: 0 + 2 = 2 -1w = 2 Divide each side by '-1'. w = -2 Simplifying w = -2
| 3n+10=-2n-8 | | -4k-1-8k=6-5k | | 1/2(6x+4)-1/3(3-6x) | | -1/4w=-9 | | 7=n+3-5n | | 235=60X | | a+x=5a | | 10-4t=-6t | | 63-3=n-5 | | 2(3r-3)=-22+8r | | -8x+3=14 | | -53-9x=35-5x | | 26=x/-5 | | 4j-3=5j | | 5(-7-6n)=-10-5n | | x^2+4x+8=8x+29 | | 2x=.36 | | 5/9(240) | | 3/7+2/5x=1/5x+1 | | 9h+6=10h | | -28=-x+11-(-5) | | -1/5r=-20 | | 5(t+2)=3.2k | | p^2=3p+28 | | (2x+1)*2+(x+1/2)*2=18 | | 5x+10=30whatisx | | 3x-12+2x=13 | | 11.3-72f=-3.82 | | 2k+k=-9 | | 2k=-9k^2-10 | | 11y-7y-10=73.92 | | -x^2y= |